Problemas de filosofía primera. Sobre la “discusión” Apel-Tugendhat - Dottori, Ariel (2020)
“Problems of First Philosophy. On the Apel-Tugendhat Discussion”. If we deem it pertinent to inquire into the foundation of philosophy, focusing on the study of prima philosophia becomes a task as urgent as it is necessary. In believing so, we will explore two alternatives. On the one hand, we will refer to the position of Ernst Tugendhat and, on the other hand, to that of Karl-Otto Apel. While he suggests that the place of the prima philosophia must be occupied by the philosophy of language, the latter argues that the fundamental question of philosophical anthropology - “what is man?” - is even more basic. In his view, addressing human language implies a further step: to understand it as a funda-mental element, we must first ask ourselves about the characteristics that human beings have as such. In the first two parts, we will give an account of both points of view to, finally, conclude that the differences discussed, which prima facie separate them, can be bridged.